Novel bone surrogates for cranial surgery training. (August 2017) - Hollensteiner, Marianne; Fürst, David; Esterer, Benjamin; Augat, Peter; Schrödl, Falk; Hunger, Stefan; Malek, Michael; Stephan, Daniel; Schrempf, Andreas
Abstract: Parietal graft lifts are trained on human or animal specimens or are directly performed on patients without extensive training. In order to prevent harm to the patient resulting from fast rotating machinery tools, the surgeon needs to apply appropriate forces. Realistic haptics are essential to identify the varying parietal bone layers and to avoid a penetration of the brain. This however, requires experience and training. Therefore, in this study, bone surrogate materials were evaluated with the aim to provide an anatomically correct artificial skull cap with realistic haptic feedback for graft lift training procedures. Polyurethane composites made of calcium carbonate and calcium phosphate were developed and were used to create customized bone surrogates, imitating both cancellous and cortical bone. Mechanical properties of these surrogates were validated for drilling, milling and sawing by comparison with human parietal bones. For that, surgical tool tips were automatically inserted into artificial and human bones in a customized test bench and the maximum axial insertion forces were analyzed. Axial tool insertion measurements in human parietal bones resulted in mean maximum forces of 1.8±0.5 N for drilling, 1.7±0.3 N for milling and 0.9±0.1 N for sawing. Calcium carbonate-based materials achieved higher forces than the human bone for drilling and milling, and lower forces for sawing. The calcium phosphate-based bone surrogates showed comparable axial insertions forces for all investigated tools and were identified as a suitable surrogate for drilling (p=0.87 and 0.41), milling (p=0.92 and 0.63) and sawing (p=0.11 and 0.76) of the cortical layer and the cancellous bone, respectively. In conclusion, our findings suggest, that a suitable material composition for artificial parietal bones has been identified, mimicking the properties of human bone during surgical machinery procedures. Thus, these materials are suitable for surgical training and education in simulator training. Highlights: Axial tool insertion forces were identified as suitable parameter to validate haptics of artificial bone materials compared to human bone. Four different bone surrogate materials conceited for a novel cranial graft lift simulator were proposed. Realistic haptic performance of two material mixtures confirmed their suitability for training in the field of cranio-maxillofacial surgery. Surgical experts certified realistic haptics during all procedural steps. Graphical abstract: